Påverkar suggors grymtande under digivningen smågrisarnas tillväxt? - Spjuth, Linda (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2003)
The pig is unique in the way that it gives birth to a large number of newborns in each litter. Because of this the sow has developed a special behaviour during suckling to ensure that not only a part of the litter gets all the milk. Milk is only available during milk letdown. The piglets have to massage the udder for a long time before letdown and the more piglets at the udder the sooner the milk comes. The sow has developed a special grunting pattern to let the piglets know when she is ready for suckling and to signal milk letdown. Our aim with this study was to investigate if sows have individual grunting patterns repeated over time. We also wanted to know if sows with a more distinct grunting pattern have better growth in their litters. We recorded grunting during suckling in nine sows at three occasions (two or three days after farrowing and one and three weeks after farrowing). The piglets were weighed at each occasion. We also registered the volume of the grunting during suckling. We found no correlations between sows grunting pattern and piglet growth and we could not see that sows have individual grunt patterns that repeat themselves over time.